Influence of the Gas Pressure of Plasma Nitriding on the Structural, Mechanical and Tribological Surface Properties of AISI 316L - Campos, Marcelo [UNESP]; Souza, Solange de; Davim, Joao Paulo; Souza, Sylvio Dionysio de; Olzon-Dionysio, Maristela (Univ Fed Sao Carlos, Dept Engenharia Materials, 2019)
In this paper, the influence of gas nitriding (80% H-2-20% N-2) pressure (between 3 and 7 Torr) on the modification of surface properties of AISI 316L stainless steel is examined. The structural, mechanical, tribological and electrochemical properties of the layer produced in disk samples were studied. The samples' characteristics were determined by scanning electron microscopy, X-ray diffraction, electrochemical potential curves, microhardness, roughness and wear tests. When pressure increases, the microhardness, elasticity and thickness also increase. The maximum thickness of the nitrided layer was 6.4 mu m, the hardness reached 2200 HV0.0036 and the mass loss decreased until 1% relatively to the unnitrided sample. The X-ray diffractograms showed the presence of the expanded austenite in all the samples. The correlation between these diffractograms and the corrosion results corroborate to the most recent previous conclusions of our systematic study, which evince the interconnection between the improvement of the corrosion resistance and the presence of nitrides on the top of the nitrided layer. More significant presence of such nitrides was observed for the sample nitrided at 6 Torr, whose corrosion performance was better than for the other samples. This pressure seems to be the most indicated to improve the properties under study. Moreover, the results verified not only that the sample geometry is an important factor for enhancing these properties but also that the border effect, which causes the rings on the disk border, depends on the pressure, but not on temperature or time from the plasma nitriding process.
Keywords: AISI 316L stainless steel; Plasma nitriding; Gas nitriding pressure; Tribological and Mechanical properties; Synchrotron Diffraction